Pandangan MUI terhadap Pluralisme Agama - Muhammad Nasir (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Religious pluralisme among Muslims itself raises pros and cons, acceptance on the one hand and resistance on the other. Supporters of religious pluralisme argue that this idea is a necessity in the midst of Indonesia's pluralistic condition. Opponents of religious pluralisme are of the view that this idea is misleading, because it tends to mix up religious teachings and assumes that all religions are true. The climax of the conflict over the notion of religious pluralisme was the issuance of a fatwa by the Indonesian Ulema Council (MUI) regarding the prohibition of pluralisme, secularism and religious liberalism. This research was conducted to examine more deeply the MUI's views on religious pluralisme. This study aims to find out why some issues of religious pluralisme have received a response from the MUI and how the MUI views religious pluralisme. To examine this problem, a descriptive analysis method was used, namely a problem solving that includes recording, interpreting and analyzing MUI's views on religious pluralisme and writings related to it. The results of the research are: The issue of religious pluralisme and the development of secular and liberal thinking in Indonesia received a firm response from the MUI because pluralisme, secularism and religious liberalism were seen by the MUI as having distorted Islamic teachings and had raised people's doubts about the Islamic creed and sharia. The MUI's view of pluralisme, secularism and religious liberalism is an understanding that is contrary to the teachings of Islam. It is forbidden for Muslims to follow the notions of pluralisme, secularism and religious liberalism. In matters of aqidah and worship, Muslims must be exclusive, in the sense that it is forbidden to mix the aqeedah and worship of Muslims with the aqeedah and worship of followers of other religions. For Muslim communities who live with adherents of other religions (religious plurality), in sosial issues that are not related to faith and worship, Muslims are inclusive, in the sense that they continue to engage in sosial relations with adherents of other religions as long as they do not harm each other. Abstrak Pluralisme agama di kalangan Islam sendiri menimbulkan pro dan kontra, penerimaan di satu sisi dan resistensi di sisi lain. Para pendukung pluralisme agama berpendapat, ide tersebut adalah sebuah keniscayaan di tengah kondisi Indonesia yang majemuk. Para penentang pluralisme agama berpandangan bahwa ide tersebut menyesatkan, karena cenderung mencampuradukkan ajaran agama dan menganggap semua agama benar. Puncak pertentangan atas paham pluralisme agama adalah dengan keluarnya fatwa Majelis Ulama Indonesia (MUI) tentang haramnya paham pluralisme, sekularisme, dan liberalisme agama. Penelitian ini dilakukan untuk mengkaji lebih dalam mengenai pandangan MUI terhadap pluralisme agama. Penelitian ini bertujuan untuk mengetahui mengapa sebagian isu pluralisme agama mendapat respons MUI dan bagaimana pandangan MUI terhadap pluralisme agama. Untuk meneliti masalah ini digunakan metode deskriptif analisis yaitu suatu pemecahan masalah yang meliputi pencatatan, penafsiran dan analisa terhadap pandangan MUI terhadap pluralisme agama dan tulisan-tulisan yang berkaitan dengannya. Adapun hasil dari penelitian adalah: Isu pluralisme agama dan berkembangnya pemikiran sekuler dan liberal di Indonesia mendapat respons MUI dengan tegas karena pluralisme, sekularisme dan liberalisme agama dipandang oleh MUI telah membelokkan ajaran Islam dan telah menimbulkan keraguan umat terhadap akidah dan syariat Islam. Adapun pandangan MUI terhadap pluralisme, sekularisme dan liberalisme agama adalah paham yang bertentangan dengan ajaran agama Islam. Umat Islam haram mengikuti paham pluralisme, sekularisme dan liberalisme agama. Dalam masalah aqidah dan ibadah, umat Islam wajib bersikap eksklusif, dalam arti haram mencampuradukkan aqidah dan ibadah umat Islam dengan aqidah dan ibadah pemeluk agama lain. Bagi masyarakat Muslim yang tinggal bersama pemeluk agama lain (pluralitas agama), dalam masalah sosial yang tidak berkaitan dengan aqidah dan ibadah, umat Islam bersikap inklusif, dalam arti tetap melakukan pergaulan sosial dengan pemeluk agama lain sepanjang tidak saling merugikan.